Trade Liberalization and Investment : Firm-level Evidence from Mexico - Kandilov, Ivan T.; Leblebicioğlu, Aslı (Oxford University Press on behalf of the World Bank, 2013)
Plant-level panel data from Mexico's Annual Industrial Survey is employed to evaluate the impact of reductions in tariffs and import license coverage on final goods, as well as intermediates, on firms'investment decisions. Using data from 1984 to 1990, a period during which a large scale trade liberalization occurred, a dynamic investment equation is estimated using the system-GMM estimator developed by Arellano and Bover (1995) and Blundell and Bond (1998). Consistent with theory, the empirical analyses show that a reduction in import protection on final goods leads to lower plant-level investment, whereas reductions in tariffs and import license coverage on intermediate inputs result in higher investment. Also, firms with larger import costs experience a larger increase in investment following a reduction in import protection. On the other hand, higher markup firms lower investment more aggressively following reductions in tariffs and import license coverage on final goods.